How a 'top-performing' Asian school system formulates and implements policy: The case of Singapore. (September 2014) - Tan, Cheng Yong; Dimmock, Clive
This article analyses the paradox inherent in the 'top-performing' yet tightly controlled Singapore education system. As government controls have increased in complexity, existing policymaking conceptual heuristics in accounting for centre-periphery relationships appear inadequate. It argues that more direct government control is being replaced by 'steering through paternalism from close proximity', reflecting a more subtle centre-periphery relationship in an Asian context.